Caracterização morfo-fisiológica e identificação de fragmentos de cDNA diferencialmente expressos de tegumentos de sementes de soja com permeabilidade contrastante - Mertz, Liliane Márcia (2007)
Some works have reported the existence of contrasting soybean genotypes for physiological quality of seeds. There are such differences because of the presence of seeds with total or partial impermeability for water absorption into the coat that make them less susceptible to mechanical damages, weather adversities, deterioration by humidity and pathogen occurrence. The characteristic of semi-permeable coat can be used in programs of soybean crop breeding to be incorporated in genotypes of high production, aiming at the physiologic quality of the seed. The objectives of this study were: Identify structural differences among the coat of the genotypes CD-202 (permeable) and TP (semi-permeable); obtain fragments of genes distinguishingly expressed among the coat of those genotypes; characterize the physiological quality of soybean seeds produced. Morphologic characterization of the coats was carried out by optic microscope BX 51 with increase of 40x. In order to obtain the fragments of genes distinguishingly expressed among the coats of the two genotypes, the technique cDNA AFLP was used. The physiological quality of the seeds was obtained by germination tests and vigour (accelerated ageing and electrical conductivity). Besides, structural differences were observed among the coats of the two genotypes, however, the genotype TP presented higher thickness in the layers of the epidermis and hypodermis of the coat in relation to the genotype CD 202, beside differences in the format and organization of the cells. Regarding the molecular genetic studies, 47 fragments distinguishingly expressed in the coats in the formation of genotypes CD - 202 and TP, were identified. In agreement with the results, soybean seeds with semi-permeable coat presented better physiological quality in relation to the seeds with permeable coat.